How fisher‐influenced marine closed areas contribute to ecosystem‐based management: A review and performance indicator scorecard. Issue 5 (28th February 2017) - Kincaid, Kate; Rose, George; Devillers, Rodolphe
Abstract: A rapid review of the literature on closed areas that recognize key ecosystem‐based management (EBM) principles of fisheries and biodiversity conservation and had fisher involvement was employed to review closed areas worldwide from a fisheries perspective and to develop a scorecard that can assess their efficacy. The review provided 523 abstracts of which 19 areas from various regions worldwide had peer‐reviewed studies that met strict selection criteria. Criteria included fisher involvement, biodiversity conservation and fisheries management objectives. A repeat search without "fisher" and synonyms found, 62, 622 papers indicating that most closed area studies had no mention of any fisher involvement. The general success of the areas selected suggests that fisher involvement benefits both biological conservation and fisheries management. Fisheries and biodiversity conservation outcomes were not exclusive to any one type of management closure (e.g. MPA, Fishery Closure). Twenty‐four indicators were selected, designed to provide measurable targets. High scoring indicators included management, planning and socio‐economic indicators such as local support (100%), habitat protection (100%), conservation and fisheries objectives (100%), monitoring (91.7%) and fishers concerns (91.7%). Bio‐ecological‐based indicators scored lower in most cases for all types of areas. Fisheries closures rated as highly as the MPAs with respect to both fisheries and bio‐ecological indicators. The scorecard provided a reasonable means to evaluate management success in the light of often qualitative or missing data. Addressing the interests and utilizing knowledge of those affected by closures and familiar with the area, most often local fishers, is key to achieving management objectives.